Dietary Fructus Schisandrae extracts and fenofibrate regulate the serum/hepatic lipid-profile in normal and hypercholesterolemic mice, with attention to hepatotoxicity - Pan Si-Yuan; Yu Qing; Zhang Yi; Wang Xiao-Yan; Sun Nan; Yu Zhi-Ling; Ko Kam-Ming (Lipids in Health and Disease, 2012)
Abstract Background Schisandra, a globally distributed plant, has been widely applied to health care products. Here, we investigated the effects of dietary intake of Fructus Schisandrae chinensis (FSC), both aqueous and ethanolic extracts (AqFSC, EtFSC), on serum/hepatic lipid contents in normal diet (ND)- and high-fat/cholesterol/bile salt diet (HFCBD)-fed mice. Methods Male ICR mice were fed with ND or HFCBD, supplemented with 1 and 4% of AqFSC and EtFSC, respectively, or 0.1% fenofibrate, for 13 days. Lipids were determined according to the manufacture’s instructions. Results EtFSC, but not AqFSC, significantly elevated hepatic triglyceride (TG) in mice fed with ND. Feeding mice with HFCBD increased serum total cholesterol (TC), high density lipoprotein (HDL) and low density lipoprotein (LDL) levels as well as alanine aminotransferase (ALT) activity. Supplementation with AqFSC, EtFSC or fenofibrate significantly reduced hepatic TC and TG levels. However, AqFSC and EtFSC supplementation increased serum HDL and LDL levels in mice fed with HFCBD. Fenofibrate increased serum HDL and reduced serum LDL contents in hypercholesterolemic mice. EtFSC reduced, but fenofibrate elevated, serum ALT activity in both normal and hypercholesterolemic mice. While fenofibrate reduced serum TC, TG, and HDL levels in mice fed with ND, it increased serum HDL and reduced serum LDL and TC levels in mice fed with HFCBD. Hepatomegaly was found in normal and hypercholesterolemic mice fed with diet supplemented with fenofibrate. Conclusions Feeding mice with AqFSC and EtFSC ameliorated the HFCBD-induced hepatic steatosis. In addition, EtFSC may offer protection against hepatic injury in hypercholesterolemic mice.